2020
DOI: 10.1038/s41598-020-74011-1
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of eNOS by L-NAME resulting in rat hind limb developmental defects through PFKFB3 mediated angiogenetic pathway

Abstract: l-arginine/NOS/NO signaling pathway plays a critical role in controlling variety of vascular diseases. However, whether NOS inhibition by L-NAME suppresses late embryonic development is undefined. The aim of this study is to determine whether NOS inhibition by L-NAME is critical for late embryonic rat hind limb development. The pregnant rat at E13.5 administrated L-NAME by consecutive intraperitoneal injection. The embryos been harvested from E16.5 to E 20.5. Hematoxylin and Eosin Staining, Immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
10
1
Order By: Relevance
“…Furthermore, as shown in Figure 3 B, a left shift in the dose-response curve with acacetin exhibiting a greater endothelium-dependent vessel relaxation was detected in WKY rats. Therefore, the above results suggested that acacetin improved vasodilation through activating the NO mediated pathway [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as shown in Figure 3 B, a left shift in the dose-response curve with acacetin exhibiting a greater endothelium-dependent vessel relaxation was detected in WKY rats. Therefore, the above results suggested that acacetin improved vasodilation through activating the NO mediated pathway [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was reported that AD-like symptoms in Tg-SwDI mice worsened with pharmacologically induced chronic HTN ( Kruyer et al, 2015 ). In this study, the endothelial nitric oxide synthase (eNOS) inhibitor, L-NAME ( Wu et al, 2020 ) was used. In similar studies, HTN was pharmacologically induced by eNOS inhibition in conjunction with administration of angiotensin II in the Tg2576 mouse model of AD-like pathology ( Passos et al, 2016 ; Nyúl-Tóth et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…NO is an important free radical species that is important in embryonic development. The activity of NO and NOS is necessary for embryos to initiate the formation of Frontiers in Pharmacology frontiersin.org the vasculature, and inhibition of NOS can lead to developmental defects or death of the embryo (Wu et al, 2020;Hitchler and Domann, 2021). Nuclear receptors play a very important role in the regulation of the final stage of ovarian follicle growth.…”
Section: Gene Ontology and Pathway Enrichment Analysis Of Infertility...mentioning
confidence: 99%